Monurelle Biogel® vaginal gel in the treatment of vaginal dryness in postmenopausal women. (3rd September 2017) - Nappi, R. E.; Cagnacci, A.; Becorpi, A. M.; Nappi, C.; Paoletti, A. M.; Busacca, M.; Martella, S.; Bellafronte, M.; Tredici, Z.; Di Carlo, C.; Corda, V.; Vignali, M.; et al.
Abstract: Objectives: To evaluate efficacy, tolerability and safety of Monurelle Biogel ® vaginal gel for treatment of vaginal dryness. Methods: Multicenter, national, randomized, controlled vs. no-treatment, open-label study. Ninety-five postmenopausal women were randomized (48 to Monurelle Biogel ® and 47 to no treatment). Primary endpoint was the change of Verbal Rating Scale (VRS) total score of vaginal atrophy (VA) symptoms after 8-week treatment. The main secondary endpoints were VRS single-item score, Vaginal Health Index (VHI) score, Maturation Index (MI), Female Sexual Function Index (FSFI), and Female Sexual Distress Scale-Revised (FSDS-R). Results: The VRS total score was statistically significant in favor of the treatment group on day 28 ( p = 0.001) but not on day 56 ( p = 0.064). By excluding women who were not sexually active, the total VRS scores reached the criteria for clinical success in 27/43 subjects (62.8%) in the control arm and in 38/46 subjects (82.6%) in the treatment arm ( p = 0.035) on day 56. The VHI score significantly changed in the active arm (4.71 ± 4.85 vs. 0.28 ± 1.71) ( p < 0.001) on day 56. Even the MI significantly improved, with an increase in the percentage of superficial cells ( p = 0.01). The improvements in both VHI and MI were still present at the follow-up visit after the discontinuation of the treatment (day 84). Sexual function and distress showed a statistical significant difference on day 56. Conclusions: Monurelle Biogel ® vaginal gel applied twice daily for 8 weeks is effective in relieving vaginal dryness and other VA symptoms. Such a clinical meaningful effect persists at least 4 weeks and is supported by an improvement in the vaginal environment. Trial Registration clinicaltrials.gov Identifier: NCT02994342